PENGARUH PENERAPAN E-PROCUREMENT DAN PENGENDALIAN INTERNAL TERHADAP PENCEGAHAN FRAUD PENGADAAN BARANG DAN JASA DI PROVINSI ACEH - Iffah Khairunnah; Nadirsyah Nadirsyah (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This research aims to determine the effect of the implementation of e-procurement and internal control on the prevention of fraud in the procurement of goods and services in Aceh Province. The operational variable used is the implementation of e-procurement and internal controls as the independent variable. The dependent variable is the prevention of procurement fraud. Populations in this research are all SKPD/A in Aceh Province or around 1,056 SKPD/A in Aceh Province. The sampling technique used is random sampling. In this study, field data were collected from first-hand observations to identify research problems. The respondents were employees or officials in charge of the goods or services procurement in the institutions in which they worked. Questionnaires were distributed to up to 150 respondents. A structural equation model (SEM) based on the partial least squares (PLS) test performed to test the hypothesis with WarpPLS 6.0 software. This study indicates that e-procurement and internal control have a partially positive effect on the prevention of fraud in government agencies in the province.